A need analysis of Perlis tourism employees in learning Arabic for tourism purposes - Duniya, Nur Amnah; Abd Hamid, Mohd Azrul Azlen; Sahrir, Muhammad Sabri; Ibrahim Youssef, Mohamed Abdelrahman (NUN Gemilang Enterprise, 2025)
Malaysia’s tourism sector has succeeded in term of tourist’s arrival and receipts significantly. Perlis, as the northern rising hub for tourism, holds a strategic potential in attracting Arabic-speaking travelers from the middle east and beyond for it strategic location by the border of Thailand and its proximity to Langkawi Island, a popular tourists’ destination among Arab tourists. Apart from leveraging its unique attractions, nature, and cultural heritage, Arabic language competency among tourism employees is acknowledged as a strategy for the tourism sector development. This study conducts a need analysis to examine the Arabic language learning needs among tourism employees in Perlis, aiming to bridge the linguistic gaps and eliminating language barriers. This study adapted mixed-method approach using questionnaire that distributed to 120 tourism employees across Perlis and interview with the tourism stake holders. The analysis revealed a strong demand for Arabic language skills in Perlis tourism, particularly in vital areas such as hospitality, customer service and cultural interactions due to communication challenges and language barriers between tourism employees and Arabic-speaking tourists. This research offers practical recommendations for curriculum development in teaching Arabic for tourism purposes tailored to the real needs in fostering communication efficiency, enhancing service quality and improving tourism experiences, thus strengthening its position as a preferred destination among Arabic-speaking tourists in the region